Molecular cytogenetic analysis and the establishment of a cell culture in the fish species Hollandichthys multifasciatus (Eigenmann & Norris, 1900) (Characiformes, Characidae) - Soares, Leticia Batista [UNESP]; Paim, Fabilene Gomes [UNESP]; Ramos, Lucas Peres [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Soc Brasil Genetica, 2021)
Hollandichthys is a fish genus of the family Characidae that was until recently considered to be monotypic, with cytogenetic, morphological, and molecular data being restricted to a few local populations. In the present study, the karyotype of a population of Hollandichthys multifasciatus was analyzed using classical and molecular cytogenetic approaches for the investigation of potential markers that could provide new perspectives on the cytotaxonomy. H. multifasciatus presented a diploid number of 2n=50 chromosomes and a karyotype formula of 8m+10sm+32st. A single pair of chromosomes presented Ag-NORs signals, which coincided with the 18S rDNA sites visualized by FISH, whilst the 5S rDNA sequences were mapped in two chromosome pairs. The distribution of the U snRNA genes was mapped on the Hollandichthys chromosomes for the first time, with the probes revealing the presence of the U1 snDNA on the chromosomes of pair 20, U2 on pairs 6 and 19, U4 on pair 16, and U6 on the chromosomes of pair 11. The results of the present study indicated karyotypic differences in comparison with the other populations of H. multifasciatus studied previously, reinforcing the need for further research to identify isolated populations or the potential existence of cryptic Hollandichthys species.
Keywords: Neotropical fish; cell culture; chromosomes; FISH; repetitive DNAs